2020
DOI: 10.1038/s41564-020-0705-1
|View full text |Cite
|
Sign up to set email alerts
|

Structure of polymerized type V pilin reveals assembly mechanism involving protease-mediated strand exchange

Abstract: Structure of polymerized Type V pilin reveals assembly mechanism involving protease-mediated strand-exchange

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 57 publications
2
56
0
Order By: Relevance
“…The cross-linking of these mutants with a crosslinking agent, dithio-bis-maleimidoethane, led to an increase in the molecular mass of FimA, which corresponded to the molecular mass of the anchor strand, and this effect was reversed upon the addition of β-mercaptoethanol. 88 These results indicate that pilins are anchored to the cell surface even after RgpB cleavage, which facilitates a smooth reaction between pilins. We also observed that the FimA polymer can be generated using a mouse-derived arginine-specific protease instead of RgpB, which suggests that only the proteolytic function of RgpB is a prerequisite for FimA polymerization (Shibata et al, unpublished data; Figure 4).…”
Section: Sortase-dependent Pilimentioning
confidence: 76%
See 2 more Smart Citations
“…The cross-linking of these mutants with a crosslinking agent, dithio-bis-maleimidoethane, led to an increase in the molecular mass of FimA, which corresponded to the molecular mass of the anchor strand, and this effect was reversed upon the addition of β-mercaptoethanol. 88 These results indicate that pilins are anchored to the cell surface even after RgpB cleavage, which facilitates a smooth reaction between pilins. We also observed that the FimA polymer can be generated using a mouse-derived arginine-specific protease instead of RgpB, which suggests that only the proteolytic function of RgpB is a prerequisite for FimA polymerization (Shibata et al, unpublished data; Figure 4).…”
Section: Sortase-dependent Pilimentioning
confidence: 76%
“…Immunoelectron microscopy with anti-His tag antibody revealed that the N-terminal His tag of recombinant FimA, which is separated from FimA upon cleavage by RgpB protease, is detected at one end of the FimA polymer, which suggests that the N-terminal anchor strand of FimA remains embedded in the groove even after RgpB cleavage. 88 We found that FimA that lacks the last amino acid residue tryptophan at the 383rd position (FimA [Δ383]), which cannot polymerize, is located on the cell derivatives with cysteine pairs in the anchor strand and its neighboring strands after substituting intrinsic cysteines with alanines. The cross-linking of these mutants with a crosslinking agent, dithio-bis-maleimidoethane, led to an increase in the molecular mass of FimA, which corresponded to the molecular mass of the anchor strand, and this effect was reversed upon the addition of β-mercaptoethanol.…”
Section: Sortase-dependent Pilimentioning
confidence: 99%
See 1 more Smart Citation
“…As a final cleavage step to release the assembled filaments from the membrane, a yet unidentified hydrolase may act upon UMOD, as small amounts of the CTP could still be detected in MS/MS spectra after trypsin digestion of mature filaments ( Figure 4—figure supplement 1 ). This UMOD assembly model is analogous to the recently proposed assembly mechanism of filamentous type V pili, in which assembly is linked with proteolytic release of pilus subunits from the outer bacterial membrane ( Shibata et al, 2020 ). During the preparation of this manuscript, a related preprint article on the cryo-EM structure of the UMOD filament core was published ( Stsiapanava et al, 2020 ).…”
mentioning
confidence: 73%
“…The elongated ZP linker establishes an intricate and extensively enchained scaffold for filament build-up from mature UMOD monomers. Reminiscent of donor strand complementation in subunit-subunit interactions of pili assembled via the chaperone-usher pathway ( Waksman, 2017 ) or the more recently discovered type V pili ( Shibata et al, 2020 ), formation of the UMOD filament involves a β-sheet complementation mechanism extending across enchained ZP modules ( Figure 2A ). Specifically, the extended linker between ZPN and ZPC in each monomer is comprised of three separate β-strands: Lβ 1 , Lβ 2 , and Lβ 3 (residues 430‒435, 438‒441, and 446‒452, respectively), where Lβ 1 and Lβ 2 of subunit n complement the fold of ZPC of subunit n‒1 (ZPC -1 ), and Lβ 3 extends the IG-fold of ZPN of subunit n+1 (ZPN +1 ) ( Figure 2B ).…”
mentioning
confidence: 99%